Ces villes-là: Actualité de Colette Pétonnet - Blanc-Chaléard, Marie-Claude; Parsapajouh, Sepideh; Raulin, Anne (Le social et le politique, 2018)
How can anthropology make a difference?The work of Colette Pétonnet (1929-2012) is an answer to this question. The challenge of this book is to give an account of it, by reinterviewing the singularity of her approach and by showing its topicality in contemporary research. Anchored in the French ethnological tradition, but developed in the then atypical terrain of the French suburbs, her work was pioneering in its time and remained solitary for a long time, even though she founded with Jacques Gutwirth in 1983 the Urban Anthropology Laboratory of the CNRS.Without taking a militant or even committed perspective, Colette Pétonnet, who had become intensely acclimatized to the reality of Moroccan cities, proposed another vision of the urban and the human, a decentering of the gaze that continued her critical revolution around the world, pleading for an effective displacement of conceptions and sensibilities. His approach is exemplary of an ethnology of the close, showing lucidly what the city conceals, ignores or prefers to reject; an anthropology that intends to shake up and change perceptions.The legacy of this approach can be seen in this book, many of whose contributions bear witness to the way in which, following his example, researchers have been able to learn the lessons of true risk-taking, applied to territories near and far. By confronting the past context of the first works on precarious housing and these new perspectives on the diversity of urban life in today's world, specialists from different disciplines offer an original tribute to the work of Colette Pétonnet. Comment l’anthropologie peut-elle faire bouger les choses ?L’œuvre de Colette Pétonnet (1929-2012) est tout entière une réponse à cette question. L’enjeu de cet ouvrage est d’en rendre compte, en réinterrogeant la singularité de sa démarche et en donnant à voir son actualité dans la recherche contemporaine. Ancrée dans la tradition ethnologique française, mais élaborée sur le terrain alors atypique des banlieues françaises, son œuvre fut en son temps pionnière et resta longtemps solitaire, même si elle fonda avec Jacques Gutwirth en 1983 le Laboratoire d’anthropologie urbaine du CNRS.Sans s’inscrire dans une perspective militante, ni même engagée, Colette Pétonnet, qui s’était intensément acclimatée à la réalité des villes marocaines, a proposé une autre vision de l’urbain et de l’humain, un décentrement du regard qui poursuivit sa révolution critique autour du monde, plaidant pour un déplacement efficace des conceptions et des sensibilités. Son approche est exemplaire d’une ethnologie du proche, faisant voir lucidement ce que la ville occulte, ignore ou préfère rejeter ; une anthropologie qui entend secouer et changer les perceptions.On peut en saisir l’héritage dans cet ouvrage, dont nombre de contributions témoignent de la façon dont, à son exemple, les chercheur.e.s ont su s’approprier les leçons d’une vraie prise de risque, appliquée à des territoires proches ou lointains. En confrontant le contexte passé des premiers travaux sur l’habitat précaire et ces regards neufs sur la diversité de l’urbain dans le monde d’aujourd’hui, des spécialistes de différentes disciplines proposent un hommage inédit à l’œuvre de Colette Pétonnet.